¿Expropiación encubierta? Análisis en torno a la regulación y el impacto de la servidumbre minera en el Perú - Hernández Bernos, Valentina (2025)
The regulation of mining easement in Peru has sparked debate regarding its impact on property rights. While expropriation for mining purposes cannot be implemented under the current constitutional framework, article 37 of the Consolidated Text of the General Mining Law, which allows it to be requested, has not been expressly repealed. In this context, mining easement emerges as an apparent alternative for mining concessionaires to request access to the land of those who hold surface rights within their concession. However, its application is very unlikely in practice due to procedural complexity, landowner opposition, and regulatory unpredictability. This paper examines the current legal framework of mining easement and its relationship with expropriation, analyzing the key differences between these legal figures and their impact on private property. Furthermore, it reviews the main doctrinal perspectives on whether mining easement constitutes hidden expropriation or remains a distinct legal mechanism with limited but non-definitive effects on property rights. Finally, proposals are presented to improve the regulation of mining easement in Peru, aiming to create incentives for its use while ensuring the protection of property rights for landowners. These proposals include legal amendments, improvements in the administrative procedure, and more adequate compensation mechanisms for affected property owners. This seeks to reduce legal uncertainty, promote the efficient use of mining servitude, and prevent it from effectively functioning as hidden expropriation.